Efficacy Testing of Paenibacillus spp. Against Penetration, Hatching and Survival of the Root-Knot Nematode (Meloidogyne chitwoodi) and the Root Lesion Nematode (Pratylenchus penetrans) - Tripathi, Niru (Journal of the Plant Protection Society, 2018)
Root-knot and root lesion nematodes are economically very important nematodes. They cause severe damage every year to a wide variety of crops. The use of chemical nematicides is one of the most widely used control measures for nematode management but their negative effect on health and environment and ineffectiveness after prolonged use have led to a need of safe and more effective control options. Biological control could be the best alternative option to chemicals. Experiment was conducted in the year 2016under in vitro conditions at laboratory of ILVO, Belgium. Application of Paenibacillus spp. with two different suspensions (10% and 100%) was found effective and caused significant reduction in root penetration, hatching from eggs and substantial mortality of juveniles in both Meloidogyne chitwoodi and Pratylenchus penetrans. Increased concentration with increased exposure duration increased the mortality of both species. Great reduction in hatching of both M. chitwoodi and P. penetrans was observed in 100% bacterial suspension and to a lesser extent in 10% bacterial suspension. For M. chitwoodi only 4.56% hatching was observed when egg masses were exposed to 100% bacterial suspension and 15.5% hatching was reported for P. penetrans in 100% bacterial suspension. Ninety two percentage of M. chitwoodi juveniles found dead after 6 hours and 99.2% after 24 hours in 100% bacterial suspension. For P. penetrans this was 78.2% after 6 hours and 100% after 24 hours.